Analisis Faktor-Faktor yang Mempengaruhi Pengangguran Usia Muda di Indonesia - Witta, Sri Rahma; Handra, Hefrizal (Jurnal Informatika Ekonomi Bisnis, 2025)
The high rate of youth unemployment in Indonesia is one of the major issues that the country is facing and requires serious attention from the government. The purpose of this study is to identify the factors that influence youth unemployment in Indonesia during the period from 2020 to 2021 across 34 provinces. A panel data regression using the Random Effects approach was employed as the analytical method. This study aims to analyze the impact of work experience, place of residence, and marital status on youth unemployment. The findings indicate that, collectively, work experience, place of residence, and marital status have a significant effect on the youth unemployment rate. However, when examined individually, only work experience and place of residence are found to have a significant influence on youth unemployment. Work experience has a negative and significant impact, indicating that individuals with prior work experience are less likely to be unemployed. In contrast, place of residence has a positive and significant effect, suggesting that certain living environments may increase the likelihood of unemployment among youth. Meanwhile, marital status does not have a statistically significant influence on youth unemployment in the 34 provinces of Indonesia during the 2020–2021 period.